1984
DOI: 10.1679/aohc.47.359
|View full text |Cite
|
Sign up to set email alerts
|

A transmission electron microscopic study on sinusoidal cells of guinea pig liver, with special reference to the occurrence of a canalicular system and "pored domes" in the endothelium.

Abstract: Summary.Hepatic sinusoidal cells in the guinea pig were examined by transmission electron microscopy (TEM). A meandering Canalicular system was detected in the sinusoidal endothelial cell both in thicker portions of cytoplasmic extensions and in small areas of the perikaryon.It consisted of meandering canaliculi with vacuolar expansions and constrictions, which penetrated the endothelial cytoplasm, forming as a whole a network.The canaliculi possessed more than two openings which usually communicated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
2
15
1
Order By: Relevance
“…The structural details of the alveolus fenestratus endothelialis of the normal mouse kidney in the present study is basically the same as the simple two or three fold stratified laminae fenestratae in normal rats, guinea pigs and rabbits already reported by others (WOLFF and MERKER,1966;YOSHINARI and FUJITA, 1982;NOZAKI and MIY0SH1, 1984;OHATA et al, 1984;FUJITA and MIYOSHI, 1985), although, the frequency and development of the structure are much more extensive in mice. This constant appearance, regardless of species difference, suggests that the alveolus fenestratus is not an artifact but represents some general and fundamental feature of the fenestrated endothelial cell.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The structural details of the alveolus fenestratus endothelialis of the normal mouse kidney in the present study is basically the same as the simple two or three fold stratified laminae fenestratae in normal rats, guinea pigs and rabbits already reported by others (WOLFF and MERKER,1966;YOSHINARI and FUJITA, 1982;NOZAKI and MIY0SH1, 1984;OHATA et al, 1984;FUJITA and MIYOSHI, 1985), although, the frequency and development of the structure are much more extensive in mice. This constant appearance, regardless of species difference, suggests that the alveolus fenestratus is not an artifact but represents some general and fundamental feature of the fenestrated endothelial cell.…”
Section: Discussionsupporting
confidence: 86%
“…This structure is assumed to represent a `small pore system' proposed by physiologists in relation to the transendothelial transport mechanism (LANDIS and PAPPENHEIMER,1963). However, the occasional occurrence of the stratified lamina f enestrata has been reported in the glomerular capillary of both the rat and rabbit kidney (WOLFF and MERKER, 1966;YOSHINARI and FUJITA, 1982;FUJITA and MIYOSHI, 1985), and in the sinusoidal endothelium of the liver and adrenal cortex of monkeys and guinea pigs (NOZAKI and MIYOSHI, 1984;OHATA et al, 1984). Furthermore, the lamina fenestrata has been described as occurring even on the thickened perikaryal portions of the glomerular endothelium of the kidney, designated as pored domes (YOSHINARI and FUJITA, 1982).…”
mentioning
confidence: 99%
“…In our previous transmission electron microscopic (TEM) study on the sinusoidal cells of guinea pig livers (OHATA et al, 1984), we demonstrated a meandering canalicular system in the thicker portion of the cytoplasmic extension and in the perikaryonal cytoplasm of the endothelial cell. In addition, the "pored domes", as first revealed by FUJITA and his collaborators (FUJITA et al, 1976;Y0sHINARI and FUJITA, 1982) by scanning electron microscopy (SEM) in the glomerular endothelial cells of the rat and rabbit kidney, were also found in the sinusoidal endothelial perikaryon of guinea pig livers.…”
Section: Discussionmentioning
confidence: 79%
“…The single cilium of fat-storing cells in the human liver was first reported by ITO and SHIBASAKI (1968) and later by many authors in other vertebrates (WAKE, 1971;YAMA-MOTO and ENZAN, 1975;TANUMA and ITO,1978;TANUMA et al, 1981;OHATA et al, 1982aOHATA et al, , 1984DE LEEUW et al, 1984). Its axonemal structure, however, has not been demonstrated because it is rarely encountered under the electron microscope.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, the cilia of these cells are probably immotile, and likely play a role as a sensory or chemical receptor as such cilia are assumed to do in other types of cells (CURRIE and WHEATLEY,1966;OHATA et al, 1982b). Other authors have made the same assumption about the cilia of fat-storing cells (TANUMA et al, 1981;OHATA et al, 1984), although they could not demonstrate the axonemal ultrastructure.…”
Section: Methodsmentioning
confidence: 99%